PENGEMBANGAN MEDIA INTERAKTIF BERBASIS POWERPOINT UNTUK MENINGKATKAN HASIL BELAJAR SISWA MATERI IPAS KELAS III DI SD - Arlin Rambu Iru Dauki; Nurul Anwar, Moh. Farid; Chotimah, Chusnul; Rifai, Muhanad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop an interactive PowerPoint-based learning media for Natural and Social Sciences (IPAS)  at  third-grade elementary school and to examine its validity and effectiveness in improving students’ learning outcomes. This research employed a Research and Development (R&D) method using a simplified Borg and Gall model. The subjects of this study were 29 third-grade students of SDN Merjosari 1 Malang. Data were collected through expert validation questionnaires, teacher and student response questionnaires, and learning outcome tests in the form of pretest and posttest. The results showed that the developed media achieved a high level of validity, with material expert validation at 93%, media expert at 96%, and language expert at 80%, categorized as valid to highly valid. The trial results indicated that the teacher response reached 94% (very good category), while student responses reached 80% (good category). Furthermore, the implementation of the interactive PowerPoint-based media effectively improved students’ learning outcomes, as indicated by the increase in posttest scores compared to pretest scores. In addition, the media enhanced students’ motivation, engagement, and participation in the learning process. In conclusion, the developed interactive PowerPoint-based learning media is valid, effective, and feasible for use in IPAS learning at the elementary school level.